The burn injury transfer feedback form: A 16 year Australian statewide review of burn inter-hospital transfer. Issue 4 (June 2023) - Haines, Morgan; Sritharan, Thanya; Darton, Anne; Wijewardana, Aruna; Elfleet, Diane; Welsh, Kate; Cassidy, Meredeth; Soliman, Bish; O'Neill, Shane; Cha, Jeon; Vandervord, John; Harish, Varun
Abstract: Introduction: Modern burn care is centralised, and studies show that early, prompt referral to dedicated burn services improve clinical outcomes. We describe the use of a novel clinical instrument, the burn injury Transfer Feedback Form, to support and educate referring clinicians about the early assessment and management of burn injuries. Since 2005, Transfer Feedback Forms have been completed for all burn-injured patients with inter-hospital transfer to a specialised burn unit in the state of New South Wales (NSW), Australia. The aim of this study was to review physiological, procedural, and system or process issues in the care of both adult and paediatric burn-injured patients needing retrieval and transfer in NSW as identified by the Transfer Feedback Form. Secondary objectives were to determine any significant differences in these parameters between metropolitan and regional or remote referring institutions, and if any improvements occurred in these parameters over time. Methods: This was a retrospective analysis of all patients who were transferred to a burn unit in NSW between July 2005 and July 2021 using their prospectively completed Transfer Feedback Forms. Patients were divided into metropolitan and non-metropolitan referral sources based on geographic location. Clinical issues or deficiencies identified during each patient transfer were then classified into various groups. To determine if transfer-related clinical concerns had changed with time, two distinct periods before and after 2015, when the NSW Trauma App was introduced, were analysed. We compared trends in frequency of transfer-related concerns before and after App introduction by using interrupted time series analysis. Results: A total of 3233 patients had Feedback Forms submitted during the 16-year period. We included 929 children (28.7%) and 2304 adults (71.3%). Transfer-related clinical issues were identified in 904 adults (39.0%) and 484 children (52.0%). In both adult and paediatric patients, the most common transfer-related clinical deficiency was in relation to burn size estimation with 525 patients (43.7%) and 207 patients (30.6%), respectively. Between the time periods analysed, the number of issues arising during inter-hospital transfer fell significantly for both adults (from 46.1% to 26.1%; p < 0.05) and children (from 55.3% to 40.7%; p < 0.05). Segmented regression analysis demonstrated a significant break in the rate of transfer-related clinical issues in 2014 (p < 0.05) and 2015 (p < 0.01) for adults. Accurate body surface area estimations also increased significantly by 53% and 50% for adults and children (p < 0.05 for both), respectively, after 2015. Conclusion: Our analysis indicates that the early care of burn-injured patients undergoing inter-hospital transfer is associated with clinical, technical, and logistical challenges. However, introduction of the burn injury Transfer Feedback Form has been associated with improvements in early burn care by referring centres both temporally and geographically. Smartphone-based applications such as the NSW Trauma App have also probably contributed to these findings. Adopting these simple, inexpensive strategies into burn care systems will augment inter-hospital transfer of burn-injured patients, and improve clinical outcomes. Highlights: There are clinical and logistical challenges with burn patients undergoing hospital transfer. We describe a novel instrument for providing feedback to referring clinicians. Improvements have been seen in early burn care both temporally and geographically. Smartphone-based applications (e.g. NSW Trauma App ) have also contributed.